A novel nuclear emulsion detector for measurement of quantum states of ultracold neutrons in the Earth's gravitational field. (1st July 2022) - Muto, N.; Abele, H.; Ariga, T.; Bosina, J.; Hino, M.; Hirota, K.; Ichikawa, G.; Jenke, T.; Kawahara, H.; Kawasaki, S.; Kitaguchi, M.; Micko, J.; et al.
Abstract: Hypothetical short-range interactions could be detected by measuring the wavefunctions of gravitationally bound ultracold neutrons (UCNs) on a mirror in the Earth's gravitational field. Searches for them with higher sensitivity require detectors with higher spatial resolution. We developed and have been improving an UCN detector with a high spatial resolution, which consists of a Si substrate, a thin converter layer including 10 B4 C, and a layer of fine-grained nuclear emulsion. Its resolution was estimated to be less than 100 nm by fitting tracks of either 7 Li nuclei or α -particles, which were created when neutrons interacted with the 10 B4 C layer. For actual measurements of the spatial distributions, the following two improvements were made. The first improvement was to establish a method to align microscopic images with high accuracy within a wide region of 65 mm × 0.2 mm. We created reference marks of 1 μm and 5 μm diameter with an interval of 50 μm and 500 μm, respectively, on the Si substrate by electron beam lithography and realized a position accuracy of less than 30 nm. The second improvement was to build a holder for the detector that could maintain the atmospheric pressure around the nuclear emulsion to utilize it under a vacuum during exposure to UCNs. The intrinsic resolution of the improved detector was estimated to be better than 0.56(8) μm by evaluating the blur of a transmission image of a gadolinium grating taken by cold neutrons. The evaluation included the precision of the gadolinium grating. A test exposure was conducted to obtain the spatial distribution of UCNs in the quantized states on a mirror in the Earth's gravitational field. The distribution was obtained, fitted with the theoretical curve, and turned out to be reasonable for UCNs in quantized states when we considered a blurring of 6.9 μm. The blurring was well explained as a result of neutron refraction due to the large surface roughness on the upstream side of the Si substrate. By using a double-side-polished Si substrate, a resolution of less than 0.56 μm is expected to be achieved for UCNs.